Aerodynamic Load Reduction on a Supercritical Airfoil Using Tilted Microjets. (18th February 2023) - Xue, Cheng; Deng, Feng; Wang, Haifeng; Qin, Ning
Abstract : Microjets arranged on the wing surfaces of civil transport aircraft have been shown to have great potential in suppressing high-frequency gust loads. This paper presents a study of aerodynamic load reduction on a supercritical airfoil using tilted microjets by solving the Reynolds-averaged Navier-Stokes (RANS) equations. The numerical method was first validated against the experimental and previous numerical data. Afterward, the subsonic and transonic flowfields around the supercritical airfoil were simulated with various angled microjets. The results show that both the lift reduction and the power efficiencies significantly increase as the blowing direction shifts downstream to upstream. The movement and weakening of the shock due to the jet are observed at α > 2 ∘ in transonic flow, resulting in a drag reduction compared to the baseline airfoil. However, the transient subsonic results revealed that the upstream jet induces a strong vortex shedding, which is suppressed in transonic flows. During jet deployment, there are three distinct phases: time lag, vortex rolling-up, and rebalancing, in that order. Once it reaches the trailing edge in subsonic flows, the starting vortex rapidly modifies the load and induced a strong roll-up vortex from the pressure surface. Nevertheless, in transonic flow, the rebalancing stage contributes to a greater reduction in lift due to the additional shock movement and weakening effect.